Review on Current Management and Outcome Data of Echogenic Lung Lesions and Hydrothorax of the Fetus - Degenhardt, J.; Kohl, T.; Enzensberger, C.; Axt-Fliedner, R. (Zeitschrift für Geburtshilfe und Neonatologie, 2013)
This review focuses on the prenatal management and outcome of echogenic lung lesions and isolated hydrothorax of the fetus. We give an overview of the most common forms of echogenic lung lesions like cystic adenomatoid malformation of the lung and bronchopulmonary sequestration as well as of congenital high airway obstruction sequence. We review the occurrence, appearance, pathophysiology and natural history of these lesions. Furthermore we discuss selection criteria for intrauterine treatment and algorithms for prenatal surveillance of affected fetuses.
Keywords: echogenic lung lesions; hydrothorax; congenital high airway obstruction sequence; cystic adenomatoid malformation; bronchopulmonary sequestration